Fluorogenic platinum(iv) complexes as potential predictors for the design of hypoxia-activated platinum(iv) prodrugs - Marsh, J; Lina; Huang, S; Boulet, M; White, JRG; Martin, L; Yeomans, M; Han, H-H; Diez-Perez, I; Musgrave, R; Hammond, E; Sedgwick, A (Royal Society of Chemistry, 2024)
Hypoxia (low-oxygen) is one of the most common characteristics of solid tumours. Exploiting tumour hypoxia to reductively activate Pt(IV) prodrugs has the potential to deliver toxic Pt(II) selectively and thus overcome the systemic toxicity issues of traditional Pt(II) therapies. However, our current understanding of the behaviour of Pt(IV) prodrugs in hypoxia is limited. Here, we evaluated and compared the aryl carbamate fluorogenic Pt(IV) complexes, CisNap and CarboNap, as well as the previously reported OxaliNap, as potential hypoxia-activated Pt(IV) (HAPt) prodrugs. Low intracellular oxygen concentrations (<0.1%) induced the greatest changes in the respective fluorescence emission channels. However, no correlation between reduction under hypoxic conditions and toxicity was observed, except in the case for CarboNap, which displayed significant hypoxia-dependent toxicity. Other aryl carbamate Pt(IV) derivatives (including non-fluorescent analogues) mirrored these observations, where carboplatin(IV) derivative CarboPhen displayed a hypoxia-selective cytotoxicity similar to that of CarboNap. These findings underscore the need to perform extensive structure activity relationship studies on the cytotoxicity of Pt(IV) complexes under normoxic and hypoxic conditions.